Comparison of Bacterial Communities in the Throat Swabs from Healthy Subjects and Pharyngitis Patients by Terminal Restriction Fragment Length Polymorphism - Balaji, Kannan; Thenmozhi, Ramalingam; Sundaravadivel, Marimuthu; Pandian, Shunmugiah Karutha (Applied biochemistry and biotechnology, 2012)
Terminal restriction fragment length polymorphism (T-RFLP) analysis was applied to characterize bacterial flora present in the throats of healthy subjects and pharyngitis patients. The 16S rRNA genes of bacteria present in throat metagenome were amplified by PCR with 6-carboxy-fluorescein (6-FAM)-labeled universal forward primer (27 F) and a universal reverse primer (1513R). The 16S rDNAs were digested with restriction enzymes with 4-bp recognition sites ( Msp I or Rsa I) and analyzed by using an automated DNA sequencer. T-RFLP patterns were numerically analyzed using computer programs. From analysis of the throat bacterial community, patterns derived from Msp I and Rsa I digested samples of healthy subjects and pharyngitis patients were grouped into different clusters, though Rsa I digested samples showed some uncertainty. Pharyngitis throats generated an average species richness of 9 [±2.1 (SD)] and 10 (±2.9) for Msp I and Rsa I digests, respectively, whereas healthy throats generated 6.3 (±1.2) and 6.1 (±1.5) in Msp I and Rsa I digests, respectively. These results suggest that samples from pharyngitis patients contain an unexpected diversity of causative bacteria. The pharyngitis throats were colonized with a rich diversity of bacterial species than that of healthy throats. Using T-RFLP, we are able to detect a model bacterium, Streptococcus pyogenes SF370, and T-RF patterns were consistent with the Streptococcal T-RFLP patterns. Our study indicates that T-RFLP analysis is useful for the assessment of diversity of throat bacterial flora and rapid comparison of the community structure between subjects with and without pharyngitis.